Embryonic and planula development in the upside-down jellyfish Cassiopea xamachana - Bailey M. Steinworth; Mark Q. Martindale (EvoDevo)
Abstract Some aspects of the life cycle of the scyphozoan jellyfish Cassiopea xamachana have been described in detail. Investigations of C. xamachana have largely focused on strobilation and the unusual pattern of planuloid budding at the polyp stage, in which the body wall of the polyp forms a swimming planuloid bud that shows morphological and behavioral similarities to the planula. Here, we fill gaps in our understanding of C. xamachana life history by characterizing embryonic development and planula settlement and metamorphosis. These processes happen in a manner similar to other scyphozoans studied. Gastrulation occurs by invagination, as in many other scyphozoans. Morphological observations of planula settlement and metamorphosis resemble observations of the process in Aurelia, the other well-studied scyphozoan, though some details about germ layer fates remain unclear. We also show that homeobox genes expressed during planula development are redeployed in a similar pattern in the planuloid bud. In the newly settled polyp, one of these genes is expressed in a pattern that breaks radial symmetry, extremely unusual in a scyphozoan. Our results set the stage for more detailed molecular dissections of morphogenesis in organisms with metagenic life cycles.